Survival and prognostic factors of early-stage non-small cell lung cancer in Central and Eastern Europe: A prospective cohort study - Sheikh, Mahdi; Virani, Shama; Robbins, Hilary A; Foretova, Lenka; Holcatova, Ivana; Janout, Vladimir; Lissowska, Jolanta; Navratilova, Marie; Mukeriya, Anush; Ognjanovic, Miodrag; Swiatkowska, Beata; Zaridze, David; et al. (Cancer medicine, 2023)
BACKGROUND: Although early diagnosis and surgical resection of the tumor have been shown to be the most important predictors of lung cancer survival, long-term survival for surgically-resected early-stage lung cancer remains poor. AIMS: In this prospective study we aimed to investigate the survival and prognostic factors of surgically-resected early-stage non-small cell lung cancer (NSCLC) in Central and Eastern Europe. METHODS: We recruited 2052 patients with stage I-IIIA NSCLC from 9 centers in Russia, Poland, Serbia, Czech Republic, and Romania, between 2007-2016 and followed them annually through 2020. RESULTS: During follow-up, there were 1121 deaths (including 730 cancer-specific deaths). Median survival time was 4.9 years, and the 5-year overall survival was 49.5%. In the multivariable model, mortality was increased among older individuals (HR for each 10-year increase: 1.31 [95% CI: 1.21-1.42]), males (HR:1.24 [1.04-1.49]), participants with significant weight loss (HR:1.25 [1.03-1.52]), current smokers (HR:1.30 [1.04-1.62]), alcohol drinkers (HR:1.22 [1.03-1.44]), and those with higher stage tumors (HR stage IIIA vs. I: 5.54 [4.10 - 7.48]). However, education, chronic obstructive pulmonary diseases (COPD), and tumor histology were not associated with risk of death. All baseline indicators of smoking and alcohol drinking showed a dose-dependent association with the risk of cancer-specific mortality. This included pack-years of cigarettes smoked (p-trend = 0.04), quantity of smoking (p-trend = 0.008), years of smoking (p-trend = 0.010), gram-days of alcohol drank (p-trend = 0.002), frequency of drinking (p-trend = 0.006), and years of drinking (p-trend = 0.016). CONCLUSION: This study shows that the 5-year survival rate of surgically-resected stage I-IIIA NSCLC is still around 50% in Central and Eastern Europe. In addition to non-modifiable prognostic factors, lifetime patterns of smoking and alcohol drinking affected the risk of death and disease progression in a dose-dependent manner in this population.
Keywords: nádory plic; prognóza; Prognosis; Lung Neoplasms; Humans; lidé; mužské pohlaví; prospektivní studie; Poland; staging nádorů; Male; Prospective Studies; Carcinoma, Non-Small-Cell Lung; malobuněčný karcinom plic; Neoplasm Staging; nemalobuněčný karcinom plic; Small Cell Lung Carcinoma; Polsko